A methodology to determine reliability issues in automotive SiC power modules combining 1D and 3D thermal simulations under driving cycle profiles. (November 2019) - Matallana, A.; Robles, E.; Ibarra, E.; Andreu, J.; Delmonte, N.; Cova, P.
Abstract: Current environmental concerns and fuel scarcity are leading to the progressive introduction of Electric Vehicles (EV) in the global fleet vehicle population. This requires significant design and research efforts from scientific community and industry to provide reliable automotive electric propulsion systems. The power modules used for automotive traction inverters can be considered as central elements of such systems. As they are subject to high electro-thermal stress during operation, Design-for-Reliability (DfR) approaches should be adopted. Thus, accurate models for electro-thermal simulations are relevant since the early design stages. However, such simulations become highly time consuming and complex when accurate thermal characterization through standardized or real driving conditions needs to be provided. In this context, this work proposes a simulation methodology that combines real-time simulation for electro-thermal characterization of the whole EV propulsion system, using a 1D equivalent thermal impedance circuit, in conjunction with 3D FEM thermal simulation. In this way, an accurate thermal characterization of the power module under driving cycles with long duration (of hundreds of seconds) can be obtained without computing heavy 3D FEM simulations. The proposed procedure allows to simplify and speed up the early design stages while maintaining high accuracy in the results. Highlights: A complete electro-thermal characterization methodology provided, combining 1D real-time and 3D FEM. Reduction of 3D FEM computational load, using thermal physics and RC compact circuits. Driving cycle simulation capabilities provided with reduced computational requirements. Reliability issues can be determined by precise 3D power module heat distribution.